O15.6 Molecular Surveillance of Neisseria Gonorrhoeae Penicillin Resistance: Informing Empiric Prescribing Policy in Western Australia. (13th July 2013) - Speers, D J; Goire, N; Mak, D; Fisk, R
Abstract : Against the worldwide trend, there remain populations in the remote regions of Western Australia (WA) where the efficacy rates for penicillin may be above the World Health Organisation (WHO) 95% guideline for N. gonorrhoea drug selection. Oral amoxicillin (3g) with probenecid (1g) is used empirically in these regions. The majority of gonorrhoea diagnoses in our laboratory are performed by PCR with culture-based antimicrobial resistance surveillance limited by the lack of a representative number of isolates. We therefore implemented a world-first comprehensive molecular gonococcal surveillance of penicillin resistance in our remote populations. We tested all N. gonorrhoeae -PCR positive cases from August 2011 to July 2012 (n = 1235) using a PCR assay targeting the penicillinase-producing N. gonorrhoeae (PPNG). This represented approximately 60% of the 2092 notified WA gonorrhoea cases but 91% of cases from the remote regions. Of these regions, the Kimberley PPNG rate was 0.7%, the Pilbara 4.0%, the Goldfields 10.3%, and the Mid West 0% compared to Perth, the state capital city with 12(8–16)%. When adjustments were made for chromosomal-mediated penicillin resistance (additional 3.4%), the Kimberley and Mid West regions remained below the 5% WHO resistance threshold for penicillin. In addition, a review of the Pilbara and Goldfields regions found PPNG only in the major regional centres. Based on this data, continuation of amoxicillin with probenecid in the Kimberley region with its reintroduction into the Mid West was recommended. In the Pilbara and Goldfields amoxycillin with probenecid could be continued in remote communities but empiric treatment in the regional centres and of non-locals should employ intramuscular ceftriaxone therapy, as for other parts of WA. Our study shows that molecular surveillance of gonococcal antimicrobial resistance directly from clinical specimens is feasible and could be extended to include other targets conferring resistance to other antibacterials such as ceftriaxone.